Physical Characteristic and Sensory Profile of Lampung Robusta Coffee at Various Roasting Degree - Asiah, Nurul; David, Wahyudi; Suyantini, Kadek Enik; Nuralamsyah, Muhammad Reyshahri; Astuti, Rizki Maryam; Hidayat, Steve Ganiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Lampung Robusta coffee is one of the valuable commodities in Indonesia. It also has a critical role in the national and international coffee trade. Numerous studies have explored the roasting process and its impact on coffee quality, highlighting its importance in determining physical and sensory attributes. This study investigates Lampung Robusta coffee's physical and sensory changes subjected to varying roasting degrees, including City roast (Light to medium roast), Full City roast (Medium roast), and Italian roast (Dark roast). The findings show that roasting levels significantly affect moisture content, colour, bulk density, total dissolved solids (TDS), Brix, and pH, with p-values <0.05. Sensory analysis shows that each roasting degree creates different sensory profiles, especially aroma. City roast has nutty aromas, Full City roast has floral, smokey, and earthy aromas, while Italian roast has chocolate and spices aroma. These attributes differ from ideal coffee attributes with herbal, caramel, and fruity aromas. The ideal product also described has a sweet taste, medium body, acidic aftertaste, and sweet aftertaste. These results provide a valuable reference for optimizing Lampung Robusta coffee's roasting process and product development to achieve consumer-preferred characteristics.